(untitled) (Proceedings of International Educators Conference, 2022)
The term lacuna, which arose in the process of comparing two lexical systems, has become one of the most widely used concepts in linguistics in recent years. Today, this concept is understood as linguoculturology, linguistic and regional studies, translation studies, intercultural communication.